Studi Empiris Pengaruh Manajemen Kinerja terhadap Produktivitas melalui Kepuasan Karyawan - Ridwan Kurniawan; Sutianingsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The competition between MSMEs that is created will encourage many MSME players to start looking for ways to increase the number of sales to continue to make the maximum profit possible. Several steps will be taken, one of which is starting to pay attention to performance management and creating a more efficient and effective path. This research aims to find out whether performance management and can influence the company's productivity level. The research was conducted using a survey method with a total sample of 25 employees who were registered as workers at the Nasi Kepal Jaya Wijaya MSME, which is a fairly successful producer of packaged rice balls and side dishes in the city of Surakarta. Data were collected using a questionnaire and then scoring and interpretation were carried out using a Likert Scale. The research results show that performance management and have a big influence on the company's productivity level. The indirect influence between performance management (X) and productivity (Y) through the employee satisfaction variable (M) has a path coefficient value of: 0.673 x 0.568 = 0.328 with a significant value for the influence of X on Y through M being 0.020<0.05 and calculated t value 2.325> t table 2.048 which means there is a partial influence between the performance management variable (X) on the productivity variable (Y) through (M). This indicates that although performance management does not have a significant influence on productivity directly, the two will influence each other through employee satisfaction as mediation.